2019
DOI: 10.1136/bmj.l4680
|View full text |Cite
|
Sign up to set email alerts
|

Association of China’s universal two child policy with changes in births and birth related health factors: national, descriptive comparative study

Abstract: ObjectiveTo measure the association of China’s universal two child policy, announced in October 2015, with changes in births and health related birth characteristics.DesignNational, descriptive before-and-after comparative study.SettingEvery county in 28 of 31 provinces of mainland China.ParticipantsBirths included in two national databases: 67 786 749 births from county level monthly aggregated data between January 2014 and December 2017; and 31 786 279 deliveries from individual level delivery information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
148
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 20 publications
12
148
0
Order By: Relevance
“…However, the prevalence of ophthalmic diseases in a second child was 90%, and in third children, it was 100%, suggesting that, for the same adult individual, a greater childbearing age might not only be associated with a higher risk of disease during pregnancy and abnormal fertility, but the chance of eventually having abnormal children is also increased. Preterm birth was found to be related to whether children suffered from ophthalmic diseases, but in a large-sample study of Li HT, the increase in the number of older mothers was not found to be related to preterm birth [1]. Liu Y's research also showed the rate of preterm birth and birth weight of the second children was not affected, perhaps due to the increase in the overall quality of medical care provided in the country [2].…”
Section: Discussionmentioning
confidence: 96%
“…However, the prevalence of ophthalmic diseases in a second child was 90%, and in third children, it was 100%, suggesting that, for the same adult individual, a greater childbearing age might not only be associated with a higher risk of disease during pregnancy and abnormal fertility, but the chance of eventually having abnormal children is also increased. Preterm birth was found to be related to whether children suffered from ophthalmic diseases, but in a large-sample study of Li HT, the increase in the number of older mothers was not found to be related to preterm birth [1]. Liu Y's research also showed the rate of preterm birth and birth weight of the second children was not affected, perhaps due to the increase in the overall quality of medical care provided in the country [2].…”
Section: Discussionmentioning
confidence: 96%
“…Despite the majority of neonatal deaths attributed to preterm birth complication, and a large amount of hospital admission-based data by gestational age (GA) available in China, the whole picture of perinatal-neonatal care remains unclear due to a lack of birth population-based clinical surveys [6][7][8][9]. Although the number of Chinese annual birth population has reached 15-17 million in the past decade, with an established universal health insurance covering maternal-infant healthcare [10][11][12][13], there is a paucity of data on vital statistics of preterm births and assessment of combined effects of antenatal, peripartum and postnatal interventions on perinatal and neonatal outcome in the preterm birth and hospitalized population.…”
Section: Introductionmentioning
confidence: 99%
“…The current study aimed to depict the morbidity and mortality of whole regional preterm births and hospitalized infants strati ed by GA, investigate the role of Huai'an Women and Children's Hospital (HWCH) as the main transferal center of whole region, and verify the e cacy of perinatal interventions and the underlying neonatal morbidities of deaths. As birth population-based studies on perinatal and neonatal healthcare are still at preliminary stage in China [6,12,13], our concept and methodology of using regional birth registry data to assess death risks in hospitalized preterm population and the quality of regional perinatal-neonatal healthcare system may be helpful to re-evaluate and optimize the standard of care and health insurance policy in the transitional period of China [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…After the implementation of the universal twochild policy in 2016, experts predict that the number of births will increase signi cantly in the next ve years [11],which was estimated from 100,000 to more than 10 million each year [12]. The change in demographic structure will not only increase the number of older women, but also heighten the risk of pregnancy and the incidence of pregnant complications and comorbidities [12,13].Obstetricians are facing greater challenges. The joint management of MNM by obstetrics and the intensive care unit (ICU) is a major measure for the rescue of emergency obstetrics.…”
Section: Introductionmentioning
confidence: 99%